Monetary Policy: The Case of Industrial Output of Selected Developing African Economies - (:unkn) unknown (My University, 2022)
We evaluate the monetary policy effect on Industrial Output. Data were sourced from World Bank Data Atlas and countries Central Bank Annual bulletin for interest rate (IntR), cash reserve ratio (CRR), inflation rate (INFR), money supply (M2) and manufacturing output (MO) from 1986 to 2021. The used ARDL Co-integration, ARDL regression and ARDL Panel regression. Monetary policy has significant relationship with manufacturing output in the three-individual developing African countries; while, monetary policy was however unable to facilitate a significant change in manufacturing output of the three countries’ economies combined. Thus, industrial output is influenced by monetary policy in the individual countries but does not influence industrial growth in the combined selected developing African economies. Long run relationship exists between monetary policy and industrial output represented by manufacturing output for individual countries and the three countries’ economies combined. Hence, monetary policy has long run effect on manufacturing output of both the individual countries and the three countries combined. Regulatory authorities need to harmonize uniform African cash reserves of banks, interest rates and increase money supply that facilitates easily accessed loans and funds by manufacturing/industrial outlets to enhance manufacturing output in Africa.
Keywords: African Research